The interplay of online sexual harassment victimization, personality factors, and experiences of loneliness - Barros, Vanessa (2024)
In contemporary society, the internet plays a crucial role in enhancing connectivity among individuals. However, alongside its numerous advantages, the virtual realm presents challenges such as online sexual harassment, a prevalent issue characterized by offensive sexual messages. This study aims to explore the intricate relationship between online sexual harassment, personality traits, hostility, and loneliness. Conducted as descriptive, correlational, cross-sectional, and quantitative research, the study involved 472 participants of Portuguese nationality. The key findings underscore the significant prevalence of online sexual harassment victimization within this sample, highlighting dark personality traits, hostility, and loneliness as interconnected factors. Consequently, this study provides valuable insights into the existing literature by shedding light on the specific dynamics among the investigated variables.